Modelagem geográfica como resurso para transversalidade do planejamento de transportes - William Leles de Souza Costa (2023)
Transportation planning of critical infrastructure historically has been based on economic and strategic aspects, and also on political interests for shaping the highways and railways. These infrastructures notoriously drive human activities within regions directly intercepted, which is proved by the strong correlation between transport and economic development. The majority of the national road network was planned and built considering strategic interests that pushed occupation countryside, and the side effects of a unilateral standpoint still have been felt, especially in remote areas such as the Amazon and Cerrado biomes. Currently, there is a clear environmental regulation to be followed for new ventures, however, it is questioned whether the geographic and temporal range of the analyzes is sufficient to guarantee their success. Public, social, and environmental policies included in the transport planning process, even when respected, have not been sufficiently equipped with information capable of anticipating knowledge of future problems. Transport planning, which is intrinsically related to land use and occupation and territorial planning, currently feels the effects of the obsolescence of methodologies incompatible with the current state of the art. Indeed, this Ph.D. dissertation brings together studies and developments towards the modernization of transport planning, more specifically aimed at the geographical component of the project and analysis of socio- environmental information together with information on constructive, logistical, and economic parameters to support the complex decision-making system. Thus, two approaches were proposed, the first referring to modeling feasibility corridors already in an advanced stage of automation and the second to predictive modeling of scenarios for simulating changes in routes and, consequently, in logistic macro-basins implemented for agricultural commodities. The document presents all two models in detail to promote knowledge transfer and model replicability. The entire implementation was developed with free tools and using official public data. The implementation was entirely developed using free software and using official public data. The two models developed were applied in real-case and controversial studies. The first refers to alternative feasibility corridors in the proposal for the BR080 and BR242 segments south of the Xingú Indigenous Reserve and the second relates to vector topological modeling of routes and logistical macro-basins. The results prove the efficiency of computational modeling and its high capacity to bring together, in an organized and transparent way, a vast collection and data in a geographic range at the federal level to meet both well-known and latent demands of transport planning. Moreover, the models facilitate the transversality of the transportation planning processes with other areas such as the environment, economy, justice, and planning. The research meets the sustainable development goals 9, 13, 15, and 17 of the United Nations 2030 Agenda.